Landslides Triggered by the 1970 Tonghai Ms 7.7 Earthquake and their Distribution Characteristics. Issue 5 (October 2021) - Cui, Yulong; Pan, Junwei; Hu, Junhong; Xu, Chong
Abstract: On January 5, 1970, a Ms 7.7 earthquake occurred in Qujiang River valley, Tonghai County, Yunnan Province, China, with many induced landslides. In this study, the black-and-white KeyHole satellite images were downloaded before the earthquake on February 12 1969, and after the earthquake on March 17, 1970. Then based on the downloaded images, the visual interpretation of landslides in the earthquake intensity district with 8–10 degrees was carried out on the ArcGIS software platform. As a result, a landslide inventory composed of 640 landslides is established. The landslides are mainly distributed on both sides of the Qujiang River valley that developed along the seismogenic fault, Qujiang fault; the interpreted landslides are all large, with an area of 150–74387 m 2 . In addition, there are 384 landslides with an area of 1000–10000 m 2, accounting for 60% of the total number of landslides. Affected by the quality of the images, the interpreted earthquake landslides are larger than those of the other earthquakes, such as the 2014 Ms 6.2 Ludian earthquake and the 2015 Ms 7.8 Nepal earthquake. The seismic landslide inventory obtained in this study can provide basic data for the follow-up research. The findings have substantial implications for earthquake and seismic landslide disaster prevention and mitigation in high-earthquake intensity locations.